Review of the intertidal rove beetle tribe Liparocephalini Fenyes (Coleoptera, Staphylinidae, Aleocharinae) from Japan - Tasaku, Yuto; Ono, Hiroki; Maruyama, Munetoshi (Zootaxa, 2023)
Japanese fauna of the intertidal rove beetle of tribe Liparocephalini Fenyes, 1918 is reviewed and six genera and 26 species are recognized. A new genus, Rotundicephala Tasaku, Ono & Maruyama, gen. n., is described to include R. pacifica (Sawada, 1971) comb. n. (type species; transferred from Diaulota), R. koreana (Yoo & Ahn, 2021), comb. n. (transferred from Diaulota) and R. koheii Tasaku, Ono & Maruyama, sp. n. Four new species are described: Diaulota decipiens Tasaku, Ono & Maruyama, sp. n., which has been confused with “D. aokii”, D. orientalis Tasaku, Ono & Maruyama, sp. n., R. koheii Tasaku, Ono & Maruyama, sp. n., and Paramblopusa sumikawai Tasaku, Ono & Maruyama, sp. n. Three species, Amblopusa brevipes Casey, 1893, D. submarina Ahn, 2023 and R. koreana, are reported from Japan for the first time. We provide keys to genera and species, illustrations of mouth parts and diagnostic characteristics of each genus, and diagnostic characteristics and illustrations of the genitalia of almost all species. Biogeographical patterns of Diaulota and Rotundicephala gen. n., and the tribal range and monophyly of Liparocephalini are discussed. Three genus-group: the Liparocephalus genus-group, the Amblopusa genus-group, and the Paramblopusa genus-group are recognized in the tribe, but Baeostethus Broun, 1909 known from New Zealand is regarded as incertae sedis. The genera Ashella Klimaszewski, 2020 and Ianmoorea Ahn, 2006 are excluded from Liparocephalini.